PENGEMBANGAN BOOKLET TENTANG TIPE-TIPE STOMATA TUMBUHAN FAMILI ARECACEAE DI LINGKUNGAN FKIP UNIVERSITAS LAMBUNG MANGKURAT BANJARMASIN - Heni Jumiati; Sri Amintarti; Aulia Ajizah (Bioedukasi Jurnal Pendidikan Biologi, 2024)
A booklet is a small book containing interesting information and pictures that can be used as teaching material. The research aims to describe the development process and the quality of the Booklet development results. Booklet development uses the 4-D model by Thiagarajan, which is limited to the Develop stage, which is limited to validation tests and readability tests, and the Dissemination stage, which is limited and simple. The subjects of the research and development of the Booklet were two lecturers and nine students who had passed the Plant Anatomy course in the Biology Education FKIP, Universitas Lambung Mangkurat, Banjarmasin. The object of this research is a booklet of the types of stomata of the Arecaceae family found in the FKIP environment at Universitas Lambung Mangkurat, Banjarmasin. The results of the study and development of booklets in the suitability test obtained an average score of 4.38 (very appropriate), the feasibility test obtained an average score of 4.43 (very feasible), and the readability test by students received an average score of 4.39 (very good).